How E-Commerce companies empower the small entrepreneurs through B2B platform: A case study of ShopUp - Pretty, Mehnuma Islam (Brac University, 2021)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2021.